The Principle of Selection of Lexical Units Expressing Religious Concepts - Rakhimova Dilfuza Masharip qizi (Researchparks Publishing, 2021)
The article deals with the issues based on the description of the nature of the representation in the phraseological fund of the English and French languages of the main religious concepts of the carriers of these languages, who are historically representatives of the Catholic and Anglican confessions. An analysis of the phraseological activity of religious vocabulary of a theological nature, revealed as a result of studying the component composition of phraseological units, is given, as a result of which the author comes to the conclusion that the key features of the Catholic and Anglican wisdoms are reflected in the phraseology.